Emotionalism Within People-Oriented Software Design - Sherkat, Mohammadhossein; Miller, Tim; Mendoza, Antonette; Burrows, Rachel (Frontiers in Computer Science, 2021)
In designing most software applications, much effort is placed upon the functional goals, which make a software system useful. However, the failure to consider emotional goals, which make a software system pleasurable to use, can result in disappointment and system rejection even if utilitarian goals are well implemented. Although several studies have emphasized the importance of people's emotional goals in developing software, there is little advice on how to address these goals in the software system development process. This paper bridges the gap between emotional goals elicitation and the software system design process by proposing a novel technique entitled the Emotional Goal Systematic Analysis Technique (EG-SAT) to systematically analyse people's emotional goals in cooperation with functional and quality goals. EG-SAT allows in-depth analysis of emotional goals to build a software system and provides a visual notation for representing the analysis, which facilitates communication and documentation. EG-SAT provides traceability of emotional goals in system design by connecting the emotional goals to functional and quality goals. To demonstrate the method in use, a two-part evaluation is conducted. First, EG-SAT is used to analyze the emotional goals of potential users of a mobile learning application that provides information about low carbon living for tradespeople and professionals in the building industry in Australia. The results of using EG-SAT in this case study are compared with a professionally-developed baseline. Second, we ran a semi-controlled experiment in which 12 participants were asked to apply EG-SAT and another technique on part of our case study. The outcomes show that EG-SAT helped participants to both analyse emotional goals and gain valuable insights about the functional and non-functional goals for addressing people's emotional goals. The key novelty of the EG-SAT is in proposing an easy to learn and an easy to use technique that helps system analysts gain insights on how to address people's emotional goals. Furthermore, the EG-SAT enables system analysts to convert emotional goals to traditional functional and non-functional goals that can be analysed by existing software engineering methodologies without demanding excessive effort.